Building information modelling (BIM) in small and medium enterprises (SMEs) within Malaysian construction sector: implementation, - Toe, Wai Yan; Kong, Sio Kah (INTI International University, 2018)
Building Information Modelling (BIM) is an evolutionary technology that is emerging rapidly in the construction industry around the world where the need to implement it has become increasingly dire. However, BIM implementation progress in Malaysia has not been satisfactory. There are researches which were aimed at Malaysian construction sector in general to figure out ways and strategies to solve this issue but the needs and problems faced by the small and medium enterprises (SMEs) have been left unheard and set aside. SMEs are the backbone of a nation’s economy and the issues that are affecting them in regards to BIM implementation should be specifically studied since their capabilities and needs are distinct and diverse compared to large enterprises. This paper aims to discover the extent of BIM implementation level and barriers of BIM implementation to promote BIM implementation among the SMEs within Malaysian construction sector. Questionnaire survey based on stratified random sampling method were distributed to 300 SMEs in Malaysian construction sector and 96 of them have been collected back. Relative Importance Indices (RII), Variance and Standard Deviation (SD) were used to analyse the results. The findings reveal that BIM implementation level among the SMEs in Malaysian construction sector is only at an early stage, between Level 0 and Level 1, where paper-based formats and 2D CAD formats are the most common. The barriers hindering BIM implementation are related to cost, attitude, government involvement, awareness, expertise, nature of industry, IT, personnel, contentment, and education. In conclusion, should the most challenging barriers be revealed and controlled, the SMEs within Malaysian construction sector has a huge potential for BIM growth in the future.